Postfire Safety Investigation on Prestressed RPC Beams after Exposure to Elevated Temperatures - Yan Kai; Zhang Yao; Cai Hao; Fan Lili; Xin Zhang (Advances in Materials Science and Engineering)
Since the postfire safety of prestressed RPC beams after exposure to elevated temperatures needs to be studied and proved, this paper prepares eight smart prestressed RPC beams with intelligent sensors built in to monitor the internal temperature, force, and strain. The residual bearing tests after fire are carried out. The failure process of the beams under static load with different fire durations cover thickness of tendons, load ratio, bonded and unbonded tendons, and partial prestressing ratio, which are investigated. The load-deflection curves, crack distributions and developments, and strain variations are obtained, in addition to the damage mechanism and failure mode of the beams. The results show that the load-deflection curve of the prestressed RPC beam after fire has obviously three polylines, and the deflection points are where the cracks expand and the tendons yield. The failure procedure is the same as that of under-reinforced beams, while the height of the crushing zone is much lower than that of the balanced-reinforced beam at room temperature. The whole span deformation demonstrates a strong catenary effect, and the midspan deflection is approximately 1/40 of the effective span. The postfire safety of the bonded prestressed RPC beams is superior to that of unbonded prestressed RPC beams. The test results of this paper provide a basis for the safety performance evaluation and control of prestressed RPC beams after fire.